Clinical outcome with NOACs vs VKAs in patients with atrial fibrillation and severe chronic kidney disease: results of a retrospective, multicenter, real-world study. (25th November 2020) - Lio, V; Pasceri, V; Di Lullo, L; Russo, V; Fimiani, F; Calabro', P; Petroni, R; Grimaldi, M; Renda, G; Pignatelli, P; Romano, S; Penco, M; et al.
Abstract: Background: Patients with atrial fibrillation (AF) and severe chronic kidney disease (CKD) are at higher risk of both bleeding and thromboembolic events. Non-vitamin K antagonist oral anticoagulants (NOACs) are licensed to be used in these patients, although they were excluded from phase III controlled randomized trials comparing NOACs vs warfarin in AF. Thus, current evidence on NOACs use in such setting of patients is not definitive. Purpose: Aim of our multicenter study was to perform a real-world comparison of clinical outcome with NOACs vs vitamin K antagonist anticoagulants (VKAs) also in AF patients having an estimated glomerular filtration rate (eGFR) 15–29 mL/min. Methods: We retrospectively included a total of 266 patients receiving NOACs (N=159) or VKAs (N=107). Primary outcome measure was the cumulative incidence of the net composite endpoint including ischemic stroke, systemic thromboembolism or any bleeding. Mean follow-up was 2.6 years. Results: CHA2DS2-VASc and HAS-BLED scores at baseline were similar in the two groups (3.4±1.3 with NOACs vs 3.4±0.9 with VKAs and 3.1±1.0 vs 3.0±0.7, respectively); eGFR and hemoglobin values were also comparable (31.8±12.3 vs 32±11.9 mL/min and 10.2±2.1 vs 11.0±2.3 g/dL, respectively). NOACs were not inferior to VKAs for the primary net composite endpoint: incidence 20.7% vs 29.9%, p<0.01 for non-inferiority, p=0.11 for superiority. In proportional Cox regression model, hazard ratio for the primary outcome measure with NOACs use was 0.74 (95% CI 0.45–1.21, p=0.22). In the NOAC group there was a trend towards reduction in minor bleeding complications (p=0.08). Conclusions: Our real-world data indicate that in patients with AF and severe renal failure NOACs are not inferior to VKAs for both safety and efficacy. The use of NOACs was associated with a numerically lower incidence of minor bleeding. Funding Acknowledgement: Type of funding source: None